Pengaruh Model Pembelajaran Problem Solving terhadap Hasil Belajar Siswa pada Tema 2 Subtema 1 di Kelas III Sd Negeri 010 Lubuk Keranji - Cenia Cantri Purba; Lisbet N. Sihombing; Eva Pasaribu (Medan Resource Center, 2022)
The research benefits of plant studies come from a large population of 32 students. This theme and sub-theme use data obtained from field observations and analysis to provide benefits. The results produced X learning outcomes related to solving variable problems, while Y were related to thematic understanding. Additionally, the method used to solve these problems influenced the results provided. This study shows that when Problem Solving methods are implemented into subject matter, students learn a lot. The learning outcomes of students increased by 85.62% compared to a control group that increased by 75.31%